Kohesivitas Kelompok pada Koperasi di Kabupaten Tapanuli Utara - Juliana Nababan (MUKASI: Jurnal Ilmu Komunikasi, 2022)
In Indonesia, cooperatives are used as development agents for poverty alleviation by improving the welfare of people who have limited economic capacity through groups, for that cooperatives must continue to be fostered and developed so that they can continue to grow and develop both in quantity and quality. However, based on data on the number of cooperative units released by Badan Pusat Statistik Provinsi Sumatera Utara on February 26, 2021, Sumatera Utara decrease in the number of cooperatives. Many studies related to cooperatives have been carried out, starting from how the development of cooperatives in Indonesia, the role of cooperatives in improving community welfare, the effectiveness of cooperatives in developing a people's economy, the role of companions in the development of cooperatives and so on. However, there is still little research that examines how a cooperative can succeed and thrive, become dormant or even disband. This research aims to analyze relationship between individual characteristics and group cohesiveness in cooperatives. Group cohesiveness is an important aspect in achieving group goals because it is a determinant for the group's sustainability. The research use the theory of group communication and group cohesiveness. A quantitative correlational method is employed using the entire population (total sampling technique), namely all members of the three cooperatives located in North Tapanuli Regency. The data are collected through questionnaires and documentation with an ordinal scale on individual characteristics and group cohesiveness. The analysis results of correlation between variables, using the Spearman Rho Rank correlation test, show that individual characteristics have a significant correlation with the group cohesiveness. The individual characteristics possessed by cooperative members will reflect their personality which is manifested in the overall way the member interacts with other group members.